To the question of the originality of national consciousness in the worldview of the Kalmyks - N. Ts. Mandzhiev (Nomadic Civilization: Historical Research, 2022)
Signiﬁcant changes in deﬁnitions have taken place in the modern socio-political lexicon, for example, the concepts of national consciousness, national self-consciousness, national self-determination have been replaced by the categories of mentality, identiﬁcation. The author of the article, using new philosophical and literary terms in his research, nevertheless considers it possible to use the system of natural ideas, and in particular the traditional interpretation of historical concepts and terms of literary criticism in the description of national thinking, which has been preserved and reﬂected in folk beliefs, Buddhist religion, oral folk art and ﬁction. This article discusses the issues of the originality of national consciousness in the picture of the world of the Kalmyks. First of all, interest was shown in folk-ethical ideas, although some philosophical foundations of being were also touched upon. A special place in the mentality of the Kalmyks is occupied by the concept of fate, which reﬂects the basic concepts of national existence, based on the Buddhist religion and folk culture. The concept of fate-zayan carries the features of the Kalmyk culture, which was largely determined by the centuries-old experience of nomadic cultural creation. For the purpose of researching and posing a scientiﬁc problem, the author of the article attracted works of ﬁction by Kalmyk writers devoted to a tragic topic for Kalmyks — deportation, in which folk-ethical, Buddhist ideas about fate — zayan, about the time of change — tsagin selgyan are represented. It is traced how the movement and circumstances of the time, not always favorable to the people, aﬀect its mentality, in some cases introducing into the consciousness not the best examples of being.This article uses the methodology of not only literary analysis, but also philosophical, cultural and linguoculturological. The article is considered by the author as a statement of a scientiﬁc problem for theoretical research of literary texts in the humanities, and for the interpretation of works in the curricula of educational institutions: school, college, higher educational institutions.